(untitled) (Journal of Engineering, 2023)
Blockchain has garnered the most attention as the most important new technology that supports recent digital transactions via e-government. The most critical challenge for public e-government systems is reducing bureaucracy and increasing the efficiency and performance of administrative processes in these systems since blockchain technology can play a role in a decentralized environment and execute a high level of security transactions and transparency. So, the main objectives of this work are to survey different proposed models for e-government system architecture based on blockchain technology implementation and how these models are validated. This work studies and analyzes some research trends focused on blockchain and the future of e-governance for connecting citizens and smart cities, such as Using Blockchain in the Notarial Office (NO), using blockchain technology in the management of police complaints, exploring blockchain-enabled end-to-end security e-voting, using blockchain and smart contract technology for trusted and safe property registration and record management, and using a blockchain-enabled Vehicle Certification (BVC) framework. Finally, this work has proven that the issue of transforming governments from the traditional system to electronic governments based on blockchain technology has become an inevitable matter of time.